Criminal Spin, Self-Control, and Desistance From Crime Among Juvenile Delinquents: Determinism Versus Free Will in a Qualitative Perspective. (November 2018) - Zemel, Ofer; Einat, Tomer; Ronel, Natti
The current research is a qualitative examination of the relations between self-control and deterministic/non-deterministic perceptions of life events and the drifts into or desistance from a criminal spin among juvenile delinquents. Based on in-depth semi-structured interviews with 21 adolescents (11 active delinquents and 10 desisters), we found that both the intensification of criminal behavior and the desistance from criminal activity are gradual and connected to the reduction or acquisition, respectively, of self-control and the offenders' belief in their self-control. Criminal behavior and self-control were found to be associated with deterministic or non-deterministic perceptions of life events: the former combined with low self-control are associated with a delinquent lifestyle; the latter combined with high self-control promote the likelihood that young offenders will modify their behavior and desist from criminal behavior. The study may provide better understanding of the role of the criminal spin in the engagement or desistance from criminal behavior.